Electron attachment to CH3COCl molecule and clusters - Kocábková, Barbora; Ďurana, Jozef; Rakovský, Jozef; Poterya, Viktoriya; Fárník, Michal; Gatt, Michael; Schöpfer, Gabriel; Jung, Philipp; Ončák, Milan (RSC advances, 2025)
We investigate the electron attachment of acetyl chloride CH3COCl (AC) molecules and clusters in a molecular beam experiment and by extensive theoretical calculations. The main product of dissociative electron attachment (DEA) to the AC molecule is Cl-, which leads to the main (AC) n Cl- series in clusters. The weaker ion series identified in the cluster mass spectra correspond to (AC) n HCl2 - and hydrogen abstraction fragments [(AC) n -H]-, in full agreement with calculated energetics. We compare the present results for AC with previously studied trifluoroacetyl chloride CF3COCl (TFAC) and trichloroacetic acid CCl3COOH (TCA) molecules and clusters. DEA of the three isolated molecules results in the main fragment Cl-; however, the electron attachment to their clusters produces distinctly different cluster ions. This demonstrates that the outcomes of reactions of electrons with molecules in an environment cannot easily be predicted from the DEA of isolated molecules, and the solvent plays a key role in the process.